Plasma Levels of Aβ42 and Tau Identified Probable Alzheimer’s Dementia: Findings in Two Cohorts - Lue, Lih-Fen; Sabbagh, Marwan N.; Chiu, Ming-Jang; Jing, Naomi; Snyder, Noelle L.; Schmitz, Christopher; Guerra, Andre; Belden, Christine M.; Chen, Ta-Fu; Yang, Che-Chuan; Yang, Shieh-Yueh; Walker, Douglas G.; et al. (Frontiers in Aging Neuroscience, 2017)
The utility of plasma amyloid beta (Abeta) and tau levels for the clinical diagnosis of Alzheimer’s disease (AD) dementia has been controversial. The main objective of this study was to compare Abeta42 and tau levels measured by the ultra-sensitive immunomagnetic reduction (IMR) assays in plasma samples collected at the Banner Sun Health Institute (BSHRI) (USA) with those from the National Taiwan University Hospital (NTUH) (Taiwan). Significant increase in tau levels were detected in AD subjects from both cohorts, while Abeta42 levels were increased only in the NTUH cohort. A regression model incorporating age showed that tau levels identified probable ADs with 81% and 96% accuracy in the BSHRI and NTUH cohorts respectively, while computed products of Abeta42 and tau increased the accuracy to 84% in the BSHRI cohorts. Using 382.68 (pg/ml)2 as the cut-off value, the product achieved 92% accuracy in identifying AD in the combined cohorts. Overall findings support that plasma Abeta42 and tau assayed by IMR technology can be used to assist in the clinical diagnosis of AD.